Watermains Leakage and Outdoor Water Use Are Responsible for Significant Phosphorus Fluxes to the Environment Across the United States. Issue 3 (23rd March 2023) - Flint, Elizabeth M.; Ascott, Matthew J.; Gooddy, Daren C.; Stahl, Mason O.; Surridge, Ben W. J.
Abstract: Human activity has led to excess phosphorus (P) concentrations and the continued eutrophication of coastal and freshwaters across the United States (US). Developing more effective P management policy requires a comprehensive understanding of P sources in the environment. Public water systems across the United States widely dose water with phosphate (PO4 ) in order to control the corrosion of lead and copper within their distribution networks. Using public water system PO4 dosing facility data and target PO4 ‐P dosing concentrations, we estimate that PO4 dosing added 4–14.9 kt PO4 ‐P yr −1 into the US water distribution network in 2015. Using estimates of public water supply inputs and domestic water deliveries, we estimate that 0.7–2.6, and 0.8–3.1 kt PO4 ‐P yr −1 were then lost from the network due to watermains leakage and outdoor water use, respectively. After accounting for these fluxes, we estimate that 9.3 kt PO4 ‐P yr −1 was then returned to wastewater treatment plants (WWTPs) and accounted for up to 2.7% of the national WWTP influent P load. As sources of P to the environment, lower and upper estimates of combined watermains leakage and outdoor water use PO4 ‐P fluxes exceeded P loads to surface waterbodies from documented point sources across 461–541 counties. The exceedance of these fluxes above other major components of the US P‐budget emphasizes the need to include them in P source apportionment studies, both across the US and in other countries where public water supplies are dosed with PO4 . Key Points: Leakage and outdoor water use release up to 17% and 21% of the 14.9 kt PO4 ‐P yr −1 added to US public water supply for corrosion control Combined leakage and outdoor water use PO4 ‐P fluxes exceed point source P inputs to freshwaters across 541 counties These fluxes should be considered in P source apportionment studies and could inform localized P management practices